Pendampingan Teknis Pelaksanaan Asesmen Nasional Berbasis Komputer bagi Siswa SD Negeri 05 Palembang - Febria Sri Handayani; Dini Hari Pertiwi; Hendra Effendi; Andika Widyanto; Eka Prasetya Adhi Sugarac; Herlinda Kusmiati (Jurnal Nusantara Mengabdi, 2022)
Purpose: A community service activity related to technical assistance in the implementation of his ANBK for SD Negeri 05 Palembang students was conducted due to limited resources and required equipment. Research Methods: This activity has three phases: preparation, implementation, and evaluation. Preparations were made by conducting final coordination and site condition surveys to prepare resources and supporting equipment for conducting ANBK 2021 at SD Negeri 05 Palembang. The implementation activities were carried out using the method of technical assistance namely, Pusmenjar's simulation of its ANBK using CAT AKMBK and technical assistance in the implementation of ANBK. Evaluation is performed at each stage by collecting and summarizing data from each stage of the activity. Result: The results of this service are the participants feel prepared and comfortable during the ANBK exam and the school (SDN 05 Palembang) can administer the ANBK independently without relying on another school. Limitations: Many of the students are not fluent in reading and have just interacted with digital devices such as laptops, smartphones, and similar applications. Contribution: It is hoped that the school will be ready to face the ANBK exams for the coming year.